Pengaruh Sex Education Terhadap Tingkat Pengetahuan Seksual Pada Anak Kelas 4-6 - Ira Nurul Laili; Nadya Elyna; Dadang Kusbiantoro; Harnina Samantha Aisyah (STIKes Ibnu Sina Ajibarang, 2024)
The phenomenon currently circulating in society is the rise of cases of sexual abuse in children, and the importance of age-appropriate sex education, meanwhile those close to children feel confused about what to convey. This study aims to determine the effect of sex education on the level of sexual knowledge in children in grades 4-6 at MI.Miftahussudur 02, Parengan District, Tuban Regency. The study used a pre-experimental one group post test design. Population of all students in grades 4-6 in MI. Miftahussudur 02 Parengan District, Tuban Regency. As many as 64 respondents used SPSS 26.0 using a purposive sampling technique, the research instrument used a questionnaire, then analyzed with the Wilcoxon Signed Rank Test with a significance level of p <0.05. The results of the study showed that before being given sex education about sexual knowledge it was found that the majority (73.5%) had sufficient sexual knowledge and after sex education most (59.4%) had good sexual knowledge. The Wilcoxon test results obtained an asymp sig (2-failed) value of 0.000 (less than the value of α = 0.05%) so it can be concluded that the hypothesis (H1) in this study is accepted, where there is an effect of sex education on the level of sexual knowledge in grade 4 children -6 At MI Miftahussudur 02 Parengan District, Tuban Regency in 2023. Low understanding of sex in school-age children leads to high sexual immoral behavior and makes children victims and perpetrators of sexual violence. Providing education to children through video media is an interactive medium to increase students' understanding of sexuality.